2020
DOI: 10.3390/hydrology7030041
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Aerial Vehicles (AAVs) as a Tool for Improving the Spatial Resolution of Snow Albedo Measurements in Mountainous Regions

Abstract: We present technical advances and methods to measure effective broadband physical albedo in snowy mountain headwaters using a prototype dual-sensor pyranometer mounted on an Autonomous Aerial Vehicle (an AAV). Our test flights over snowy meadows and forested areas performed well during both clear sky and snowy/windy conditions at an elevation of ~2650 m above mean sea level (MSL). Our AAV-pyranometer platform provided high spatial (m) and temporal resolution (sec) measurements of effective broadband (310–2700 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…UAVs provide the means to resolve the spatial variability of snow albedo at high resolutions from the individual hillslope to watershed scale, and have the flexibility to be deployed at critical times during the onset of ablation at different times within a single day. These spatially distributed sets of near-surface albedo measurements can be used to supplement calibration and validation data from AWS (Burkhart et al, 2017;Ryan et al, 2017;Levy et al, 2018;Canisius et al, 2019;Sproles et al, 2020). UAV-based snow albedo measurements provide the means to bridge the scaling gap between in-situ snow albedo measurements and satellite observations (Sproles et al, 2020).…”
Section: Current Methods Of Measuring Snow Albedomentioning
confidence: 99%
See 3 more Smart Citations
“…UAVs provide the means to resolve the spatial variability of snow albedo at high resolutions from the individual hillslope to watershed scale, and have the flexibility to be deployed at critical times during the onset of ablation at different times within a single day. These spatially distributed sets of near-surface albedo measurements can be used to supplement calibration and validation data from AWS (Burkhart et al, 2017;Ryan et al, 2017;Levy et al, 2018;Canisius et al, 2019;Sproles et al, 2020). UAV-based snow albedo measurements provide the means to bridge the scaling gap between in-situ snow albedo measurements and satellite observations (Sproles et al, 2020).…”
Section: Current Methods Of Measuring Snow Albedomentioning
confidence: 99%
“…These spatially distributed sets of near-surface albedo measurements can be used to supplement calibration and validation data from AWS (Burkhart et al, 2017;Ryan et al, 2017;Levy et al, 2018;Canisius et al, 2019;Sproles et al, 2020). UAV-based snow albedo measurements provide the means to bridge the scaling gap between in-situ snow albedo measurements and satellite observations (Sproles et al, 2020). However, the utility of these validation measurements depends heavily on processing strategy.…”
Section: Current Methods Of Measuring Snow Albedomentioning
confidence: 99%
See 2 more Smart Citations
“…There have been case studies, though, that have demonstrated mapping of broadband albedo in snow-covered environments. These studies have used paired pyranometers mounted in upward-and downward-looking configurations (Webster and Jonas, 2018;Sproles et al, 2020;Mullen et al, 2022) or a single downward-looking pyranometer on the UAV and a stationary upward-looking pyranometer within the flight area (Levy et al, 2018). These measurements return a single spectrally integrated value for incident and reflected radiation, from which broadband albedo can be calculated.…”
Section: Previous Workmentioning
confidence: 99%